The methodology and practice of econometrics a festschrift in honour of David F. Hendry - Castle, Jennifer, 1979-; Shephard, Neil.; Hendry, David F. (Oxford : Oxford University Press, 2009)
Building upon, and celebrating the work of David F. Hendry, this volume consists of a number of specially commissioned pieces from some of the leading econometricians in the world. It reflects on the recent advances in econometrics and considers the future progress for the methodology of econometrics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Econometrics; Econometric models; Econometrics -- Methodology